2021
DOI: 10.1038/s41598-021-84937-9
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of interocular symmetry of corneal biometrics in Chinese myopic patients

Abstract: It is essential to know the normal range of the interocular symmetry of the cornea (ISC) for keratoconus diagnosis and corneal substitutes design. In the present study we investigated the interocular symmetry of corneal biometrics in 6,644 Chinese myopic patients from multiple ophthalmic centers. Corneal biometrics of both eyes were exported from the Pentacam instrument. Interocular symmetry of the corneal biometrics was analyzed by Spearman’s correlation test, intraclass correlation coefficient (ICC) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…The study was approved by the Institutional Review Board (IRB) of every hospital (GZ, SY, CD, WH, and HK) and conducted in agreement with the Declaration of Helsinki. The IRBs waived the need of informed consent as the study only involved review and analysis of medical records and no individual patient could be identified from the data ( 15 , 16 ). Inclusion criteria were myopic patients with a spherical equivalent (SE) ≤ −0.50 D and good quality Scheimpflug scans.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study was approved by the Institutional Review Board (IRB) of every hospital (GZ, SY, CD, WH, and HK) and conducted in agreement with the Declaration of Helsinki. The IRBs waived the need of informed consent as the study only involved review and analysis of medical records and no individual patient could be identified from the data ( 15 , 16 ). Inclusion criteria were myopic patients with a spherical equivalent (SE) ≤ −0.50 D and good quality Scheimpflug scans.…”
Section: Methodsmentioning
confidence: 99%
“…Only the right eyes of the patients were included for analysis. Exclusion criteria were coexisting corneal diseases, keratoconus, forme fruste keratoconus, severe dry eye, non-axial myopia (such as those caused by spherophakia), previous ocular trauma or surgery, uveitis, glaucoma, wearing contact lenses within the previous 2 weeks, age younger than 18 years (unstable refraction) or older than 40 years (to reduce the effects of the crystal lens on anterior chamber depth measurement) ( 15 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since there is wide variation in the normal population that define their reference ranges, they have shown suboptimal performance in discriminating normal corneas from subclinical forms of disorders [ 14 ]. This is while measures of normal fellow corneas are strongly correlated [ 15 , 16 , 17 ], contralateral eyes are highly symmetric [ 18 , 19 , 20 , 21 , 22 ], and there is consensus that lack of symmetry should be interpreted as a red flag warranting reevaluation or further testing [ 20 , 23 , 24 , 25 , 26 , 27 ]. Nonetheless, our understanding of corneal symmetry is limited to single-point metrics (e.g., elevation at the apex, corneal thickness at the thinnest point) and local indices (e.g., simulated keratometry in the steep and flat axes); the color-coded patterns have not been classified or described, and no multi-feature or global indices have been developed yet.…”
Section: Introductionmentioning
confidence: 99%